Communicating polygenic risk scores in the familial breast cancer clinic. Issue 10 (October 2021) - Das Gupta, Kuheli; Gregory, Gillian; Meiser, Bettina; Kaur, Rajneesh; Scheepers-Joynt, Maatje; McInerny, Simone; Taylor, Shelby; Barlow-Stewart, Kristine; Antill, Yoland; Salmon, Lucinda; Smyth, Courtney; McInerney-Leo, Aideen; et al.
Highlights: Polygenic risk scores (PRSs) are a new approach that can inform breast cancer risk. Consultations to provide breast cancer PRSs were mostly clinician-driven and focused on provision of biomedical information. Compared to medical practitioners, genetic counselors were more likely to utilize counselling strategies. Provision of breast cancer PRS is a complex process and new guidelines for risk communication are needed to facilitate clinical implementation. Abstract: Objective: To describe the communication of polygenic risk scores (PRS) in the familial breast cancer setting. Methods: Consultations between genetic healthcare providers (GHP) and female patients who received their PRS for breast cancer risk were recorded (n = 65). GHPs included genetic counselors (n = 8) and medical practitioners (n = 5) (i.e. clinical geneticists and oncologists). A content analysis was conducted and logistic regression was used to assess differences in communication behaviors between genetic counselors (n = 8) and medical practitioners (n = 5). Results: Of the 65 patients, 31 (47.7 %) had a personal history of breast cancer, 18 of whom received an increased PRS (relative risk >1.2). 25/34 unaffected patients received an increased PRS. Consultations were primarily clinician-driven and focused on biomedical information. There was little difference between the biomedical information provided by genetic counselors and medical practitioners. However, genetic counselors were significantly more likely to utilize strategies to build patient rapport and counseling techniques. Conclusions: Our findings provide one of the earliest reports on how breast cancer PRSs are communicated to women. Practice implications: Key messages for communicating PRSs were identified, namely: discussing differences between polygenic and monogenic testing, the multifactorial nature of breast cancer risk, polygenic inheritance and current limitation of PRSs.